UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MENANGANI PROBLEM BELAJAR SISWA DI SEKOLAH MENENGAH PERTAMA NEGERI 9 MALANG - Nurul Hikmah; Maskuri Bakri; Muhammad Sulistiono (Vicratina : Jurnal Ilmiah Keagamaan, 2019)
This research is motivated by the number of students who experience learning problems. That is, students who experience impaired concentration or are not able to concentrate in the learning process, therefore a teacher is very instrumental in arranging and determining how to teach students, especially students who experience ADHD well, in various stages of child development, so that students are able to be disciplined and responsible, and noble. From the results of research that has been written before, after researchers conducted interviews with PAI teachers, researchers got direct information to carry out interviews, based on the findings in Chapter IV, namely in the problems faced by PAI Teachers in dealing with student learning problems were the first lack of support from parents. the two children became lazy to learn the third if the test did not learn the last if they were in their own class. While the purpose of the study is to obtain information from the teacher about problematic female students. Keywords: islamic education teacher, student learning problem